2009
DOI: 10.1002/rra.1292
|View full text |Cite
|
Sign up to set email alerts
|

Substrate requirements of spawning Chinook salmon (Oncorhynchus tshawytscha) are dependent on local channel hydraulics

Abstract: Micro-scale (<0.1 channel widths) physical conditions within channels ultimately exert a strong control on habitat selection by fish species. Data are presented demonstrating that micro-habitat requirements of spawning Chinook salmon (Oncorhynchus tshawytscha) are strongly inter-related; fish utilized coarser substrate if associated with faster flow velocities. This was not observed to be controlled through a hydraulic sorting mechanism but, rather, related to the physical processes of spawning. Failure to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Because our study reaches are narrow (bankfull widths listed in Table ), and redds are rarely observed side by side in the channel (Sean Hayes, personal communication), we treat available spawning habitat as a one‐dimensional problem, ignoring the direct effects of channel width on the distribution of redds. In large channels, where redds are often aligned side by side, perpendicular to the flow (Geist et al, ; Moir and Pasternack, , ), channel width would be a necessary consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Because our study reaches are narrow (bankfull widths listed in Table ), and redds are rarely observed side by side in the channel (Sean Hayes, personal communication), we treat available spawning habitat as a one‐dimensional problem, ignoring the direct effects of channel width on the distribution of redds. In large channels, where redds are often aligned side by side, perpendicular to the flow (Geist et al, ; Moir and Pasternack, , ), channel width would be a necessary consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous habitat modeling studies have been undertaken over time in North America and Europe, first mainly for salmonids (e.g., Northcote 1984;Shirvell 1989;Wollebaek et al 2008;Moir and Pasternack 2010) but later for non-salmonids also (e.g., Melcher and Schmutz 2010). Predominantly these studies applied univariate habitat use and preference curves.…”
Section: Multidimensional Statistical Analyses For Biological Modelingmentioning
confidence: 99%
“…Coverage by movable particles and the spawning capacity of substrates predicted from Equations (4) and (7) are both potentially useful in river management, because they constrain the maximum amount of redd building a substrate can accommodate when fish are spawning en masse, in conditions that are not limited by other factors such as flow velocity and depth (Moir and Pasternack, 2010), and hyporheic flow through redds (Tonina and Buffington, 2009). This is demonstrated in Figure 4 for spawning by three Pacific salmon species across the 31 sites of Riebe et al (2014).…”
Section: Like the Expression In Equationmentioning
confidence: 99%